Analysis on Large-Scale Solar PV Plant Energy Performance–Loss–Degradation in Coastal Climates of India - Navothna, Bhogula; Thotakura, Sandhya (Frontiers in Energy Research, 2022)
This article presents a detailed analysis of the performance, rate of degradation, and power and energy loss of a 1 MWp scale solar photovoltaic (PV) plant in the academic institution GITAM (Deemed to be University), located in the coastal region of Andhra Pradesh, India. The PV plant consists of 3,078 polycrystalline PV modules of 325 Wp rating, installed on the rooftop of the institute buildings. The annual energy generated is 1684.881 MWh. In this study, performance analysis involves the calculation of efficiency, capacity factor, and performance ratio with data simulated using the PVsyst tool. Degradation analysis involves energy light-induced degradation (LID) and degradation rate (DR). The predicted result provides an estimate for optimal functioning of PV plant with an annual capacity factor, performance ratio, and energy loss of 11.3%, 87.9%, and −26%, respectively. Energy loss by light-induced degradation is predicted as −2.7%/year, and the degradation rate of module per year is −0.6% to −5%.